PERTANGGUNGJAWABAN HUKUM TERHADAP HEWAN PELIHARAAN YANG MENYEBABKAN KERUGIAN TERHADAP HEWAN PELIHARAAN LAIN SEBAGAI PERBUATAN YANG MELAWAN HUKUM - Astika Yuni, Ni Made; Eka Wisanjaya, I Gede Pasek (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 05, Juli 2014)
This paper shall be titled legal liability for pets that lead to loss of other pets as action against the law. This paper is a normative legal research that uses statutory approach. Liability laws to pets that cause harm to others as a pet which is governed by Article 1368 of the Civil Code that accountability can be imposed in the form of compensation to the owner of the animal in concerned.
Keywords: torch, legal liability, harm, pet